2018
DOI: 10.1016/j.apenergy.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Fuel utilization effects on system efficiency in solid oxide fuel cell gas turbine hybrid systems

Abstract: A computational analysis was conducted to optimize the design of a solid oxide fuel cell-gas turbine hybrid power generator, focusing on the impact that fuel utilization within the fuel cell has on system efficiency and installed costs. This is the first ever design-study considering the effect of fuel utilization on performance, as well as on the optimum power split. This hybrid system attained high electric generation efficiencies (>70%) over a wide range of operating conditions (60% < fuel utilization < 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(25 citation statements)
references
References 28 publications
5
20
0
Order By: Relevance
“…The developed model showed good agreement with the Aspen Plus model, the maximum error was 1.33% for CH 4 composition. For the second approach, the reformer performance from the developed model was compared with Reference 29 as shown in Table 3 (18)(19)(20). As shown, both models showed good agreement with the maximum error of 3.34% for H 2 O conversion rate at 873 K and 100 kPa.…”
Section: External Auto-thermal Reformer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed model showed good agreement with the Aspen Plus model, the maximum error was 1.33% for CH 4 composition. For the second approach, the reformer performance from the developed model was compared with Reference 29 as shown in Table 3 (18)(19)(20). As shown, both models showed good agreement with the maximum error of 3.34% for H 2 O conversion rate at 873 K and 100 kPa.…”
Section: External Auto-thermal Reformer Modelmentioning
confidence: 99%
“…Lumped average values were used to represent cell temperature, current density, and U f in lumped models, which could be substantially different from a more realistic distributed model result. 20,23 U f is normally an assigned number in a lumped SOFC model. However, in a distributed model, U f is a localized phenomena across the fuel cell, which should be calculated based on different operating conditions of SOFC.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the electrolyte type, FCs are categorized and utilized in the market for different applications [1,2]. Examples of FC types are; (i) Proton exchange membrane FCs (PEMFCs) [7,8], (ii) Solid oxide FCs (SOFCs) [9,10], (iii) Molten carbonate FCs (MCFCs) [11], (iv) Phosphoric acid FCs (PAFCs) [8], (v) Alkaline FCs (AFCs) [12,13] and furthermore. Specifically, the basic characteristics of the latter-mentioned types are illustrated in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, the highest exergy destruction is associated with the engine. Oryshchyn et al 21 analysed the hydrogen utilisation factor for a combined SOFC and GT cycle. The results revealed that the highest possible efficiency for the cycle would reach 75.6%, while for achieving a minimum degradation for the SOFC stack, the efficiency would inevitably reduce by 7%.…”
Section: Introductionmentioning
confidence: 99%